If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 3x + -5 = 50 Reorder the terms: -5 + 7x + 3x = 50 Combine like terms: 7x + 3x = 10x -5 + 10x = 50 Solving -5 + 10x = 50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 10x = 50 + 5 Combine like terms: -5 + 5 = 0 0 + 10x = 50 + 5 10x = 50 + 5 Combine like terms: 50 + 5 = 55 10x = 55 Divide each side by '10'. x = 5.5 Simplifying x = 5.5
| 11x+2=18-20+11x | | 11x+2=18-(20+11x) | | 2(3x-12)=36 | | 110-3x=15x+24 | | 2a^0= | | 8-9x=21-16x | | 7x-3x-50=50 | | 5x+16=3x+55 | | 2x+3x-5=20 | | 6x-2=8x-31 | | 140x^2-36x-15=0 | | 3+2=4-5 | | (7q+5)/3=(4q-30)/6 | | 6x-1=14x-9 | | x=0,8x+2496+0,64x+2496-(x+3120)+1,28x+4992-(x+3120) | | x=0,8x+2496+1,6x+2496-(x+3120)+1,28x+4992-(x+3120) | | 3120+x=0,8x+2496+1,6x+2496-(x+3120)+1,28x+4992-(x+3120) | | 4p(p-3)=8 | | 10x+-7xy+3x^2+y^2=0 | | 3x^2y-7xy^2+10xy+y^3= | | (5x-3)-(2x-4)=-(x+3)-(x-5)+(x+3) | | x=0,8x+2576+1,6x+5152+(1,6x+5152*0,8x+2576) | | 3120+x=0,8x+2576+1,6x+5152+(1,6x+5152*0,8x+2576) | | 3120+x=0,8x+2576+1,6x+5152+1,6x+5152*0,8x+2576 | | 2x=x-17.5 | | x=-53+4y | | 5x-7y=-18 | | 12x^3-x^2+16x-33=0 | | x+3120=4/5(x+3120) | | x=-25+1.25x | | 175/3=x | | 0.8(x)=(X)-20 |